Lack of Influence of Thyroid Hormone on Bone Mineral Density and Body Composition in Healthy Euthyroid Women - Zantut-Wittmann, Denise Engelbrecht; Quintino-Moro, Alessandra; dos Santos, Priscilla Nazaré Silva; Melhado-Kimura, Vaneska; Bahamondes, Luís; Fernandes, Arlete (Frontiers in Endocrinology, 2020)
Objective: The objective of this study was to evaluate whether evolution of bone mineral density (BMD) is associated with the thyroid hormone profile in a cohort of euthyroid women with no other known diseases within one year. Methods: This was a prospective cohort study conducted at the University of Campinas, Brazil. We used a database with 52 women aged 20-39 followed for one year in a family planning outpatient clinic. The inclusion criteria were body mass index (BMI) <30 kg/m2, no known diseases/medication use, fasting glucose <100 mg/dL and 2-h glucose after a 75 g oral glucose load <140 mg/dl. The women were divided into groups of normal weight (n=30) and overweight (n=22). The main outcomes were BMD measured by dual-energy x-ray absorptiometry (DXA) and thyroid hormone profile (thyrotropin TSH, free triiodothyronine FT3, free thyroxine FT4 and T3/T4 ratio); other variables were body composition (DXA), calcium metabolism markers and life habits. We used a repeated measures analysis of variance (ANOVA) and multiple regression analyses to evaluate associations. Results: At baseline data, overweight women showed a higher T3/T4 ratio, leptin, calcium, BMD in the lumbar spine and total femur, total mass, mass and percentage of fat mass than normal weight women. At 12 months, both groups had increased FT4, calcium, ALP, femoral neck BMD and total mass by time effect. The normal weight group presented a decrease of vitamin D when compared to the baseline. Increased BMD of the femoral neck was associated with moderate coffee intake, and as such, there were no associations found between this increase and the thyroid hormone profile. Leptin and ALP were associated with total mass variation, while leptin and PTH were associated with fat mass variation. The normal BMI was inversely associated with the variation of total mass, mass and percentage of fat mass, and engaging in regular physical activity was inversely associated with fat mass variation. Conclusions: In this sample of euthyroid healthy women who were both normal weight and overweight, the thyroid hormone profile was not associated with variations in bone mineral density and body composition after a one-year follow-up.